PENGARUH GLUKOSA DAN JAHE MERAH TERHADAP KARAKTERISTIK MINUMAN PROBIOTIK DARI KULIT NANAS MADU - Samsul Rizal; Suharyono Suharyono; Fibra Nurainy; Merliyanisa Merliyanisa (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
The availability of sufficient energy sources to grow lactic acid bacteria and spices addition can influence probiotic drinks' characteristics. This study aimed to study the effect of glucose and red ginger extract on honey pineapple skin probiotic drinks' characteristics. This study used a Complete Randomized Block Design (RCBD) with two factors. The first factor was glucose concentration, namely 1%, 2%, 3%, and 4% w/v, while the second factor was the concentration of red ginger extract, namely 0%, 1%, 2%, 3%, 4%, and 5% (v/v). The data were analyzed using variance analysis (ANOVA), and the differences between means were determined using the orthogonal polynomials. The results showed that glucose increased total lactic acid bacteria and pH, but decreased the preference score of taste, color, and overall reception, but did not affect those of honey pineapple probiotic juice extract's aroma. The red ginger extract increased the taste, aroma, color, and overall acceptance scores, but did not affect the pH and total lactic acid bacteria of pineapple probiotic drinks. The best probiotic drink was from 2% glucose, and 3% red ginger extract, which had 1.3 x 109 colony lactic acid bacteria /mL; total lactic acid 0.63%; pH 3.69; somewhat like the taste, somewhat like the aroma; and somewhat like overall reception.Keywords: glucose, honey pineapple peel, lactic acid bacteria, probiotic beverage, red ginger